Analisis Dampak Lingkungan, Budaya, Umkm Masyarakat Di Kawasan Wisata Air Terjun Lewi Tilu Kabupaten Bandung Barat - Maulana Ramadhan, Abdan; Ramdani, Dadan (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the impact of the Curug Tilu Leuwi Opat tourist destination on the environment, socio-cultural environment, and economic growth of the local community in West Bandung Regency. Using a descriptive qualitative approach, data was collected through interviews with five tourists, two MSMEs, and several local residents living near the tourist area. The results indicate that this tourist destination provides a significant economic contribution to micro, small, and medium enterprises (MSMEs), especially as tourist numbers increase. The socio-cultural impact is evident in changes in community behavior in terms of lifestyle, speech, and dress due to interactions with tourists, which can lead to cultural acculturation. Environmentally, cleanliness and natural preservation are considered well-maintained, supported by tourist awareness and adequate supporting facilities. Tourist satisfaction is also high due to the availability of complete public facilities. However, some local residents have voiced complaints about traffic congestion, noise, and rising prices of goods that are disproportionate to their incomes. The government, through the tourism office and Perhutani (Perhutani), is actively involved in the management of the destination, although equitable distribution of economic benefits and comprehensive community involvement remain challenges. Therefore, inclusive and sustainable community-based tourism management is crucial to ensure that all parties receive equitable benefits from tourism activities.